PENGEMBANGAN APLIKASI SMART TOUCH PRESENTER KIT UNTUK PRESENTASI INTERAKTIF - I Putu Eka Swastika; I Gede Mahendra Darmawiguna; I Made Gede Sunarya (Universitas Pendidikan Ganesha, 2014)
The use of devices such as tabletcomputers or interactive whiteboards utilizingtouch-screen technology in a presentation ofmore interactive digital presentations provide apositive impact in comparison to conventionallearning methods that use a regular whiteboard.By utilizing the wiimote remote control for theNintendo Wii game console, wiimote library,infrared LEDS and bluetooth a technologysimilar to interactive whiteboards can be develop.This study aims to 1) Design Smart TouchPresenter Kit application for interactivepresentations; 2) Implement the system desing ofSmart Touch Presenter Kit application forinteractive presentations; 3) Make an infraredLED pen that is used as an input device forSmart Touch Presenter Kit application; 4)Determine the optimal settings for the use of theWiimote to produce good detection of infraredlight.This application is developed using theWaterfall method and implemented in The C #programming language using the Visual Studioeditor. In the development of this application isalso combined with the use of the wiimote libraryfor reading data from the wiimote. Thisapplication can be run on a computer with aWindows operating system that supports the .netframework.This application has three main features: 1)Smart Touch presenter that transforms infraredcoordinate data into a computer cursor control;2) Smart Note that provide a feature to makenotes on the screen; 3) Magnifier that can beused to enlarge a specific part on the screen sothat it can be seen more clearly. The applicationis expected to help the users in deliveringpresentation to make it more interactive withaffordable cost.